Maternal health and the baby boom - Stefania Albanesi; Claudia Olivetti (Quantitative Economics, 2014)
Fertility in the United States rose from a low of 2.27 children for women born in 1908 to a peak of 3.21 children for women born in 1932. It dropped to a new low of 1.74 children for women born in 1949, before stabilizing for subsequent cohorts. We propose a novel explanation for this boom–bust pattern, linking it to the huge improvements in maternal health that started in the mid-1930s. Our hypothesis is that the improvements in maternal health contributed to the mid-twentieth century baby boom and generated a rise in women's human capital, ultimately leading to a decline in desired fertility for subsequent cohorts. To examine this link empirically, we exploit the large cross-state variation in the magnitude of the decline in pregnancy-related mortality and the differential exposure by cohort. We find that the decline in maternal mortality is associated with a rise in fertility for women born between 1921 and 1940, with a rise in college and high school graduation rates for women born in 1933–1950 relative to previous cohorts, and with a decline in fertility for women born in 1941–1950 relative to those born in 1921–1940. The analysis provides new insights on the determinants of fertility in the United States and other countries that experienced similar improvements in maternal health.
Keywords: 330; Maternal mortality; fertility choice; baby boom; human capital